Infernal devices - Reeve, Philip (New York : Scholastic Inc, 2005)
In the distant future, when fifteen-year-old Wren Natsworthy, bored with life in Anchorage, steals an Old-Tech book for a Lost Boy, she sets off a sequence of events that leads her parents, Tom and Hester, back into battle with old enemies and new.
Angela Misa
Keywords: Science fiction